2021
DOI: 10.1038/s41419-021-04048-1
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-receptor 2—a novel negative regulator of p53

Abstract: TNF-related apoptosis-inducing ligand (TRAIL) receptor 2 (TRAIL-R2) can induce apoptosis in cancer cells upon crosslinking by TRAIL. However, TRAIL-R2 is highly expressed by many cancers suggesting pro-tumor functions. Indeed, TRAIL/TRAIL-R2 also activate pro-inflammatory pathways enhancing tumor cell invasion, migration, and proliferation. In addition, nuclear TRAIL-R2 (nTRAIL-R2) promotes malignancy by inhibiting miRNA let-7-maturation. Here, we show that TRAIL-R2 interacts with the tumor suppressor protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
5
2
Order By: Relevance
“…It is noteworthy that both TRAIL-R2 and DcR1 receptors are p53 target genes [29] and, while is clear that TRAIL-R2 upregulation is depending upon p53 activation [49], the requirement of TRAIL-R2 during p53mediated apoptosis remains still unclear. However, more recently nuclear TRAIL-R2 has been shown to act as a negative regulator of p53, suggesting that it may heavily impact, for example, on tumor growth [50]. Despite these ndings, we found that the p53 expression was blunted in TRAIL-R -/mice treated with Aβ1-42, suggesting that TRAIL-R2 contributes, in turn, to p53 mediation of Aβ-induced neurotoxicity.…”
Section: Discussioncontrasting
confidence: 75%
“…It is noteworthy that both TRAIL-R2 and DcR1 receptors are p53 target genes [29] and, while is clear that TRAIL-R2 upregulation is depending upon p53 activation [49], the requirement of TRAIL-R2 during p53mediated apoptosis remains still unclear. However, more recently nuclear TRAIL-R2 has been shown to act as a negative regulator of p53, suggesting that it may heavily impact, for example, on tumor growth [50]. Despite these ndings, we found that the p53 expression was blunted in TRAIL-R -/mice treated with Aβ1-42, suggesting that TRAIL-R2 contributes, in turn, to p53 mediation of Aβ-induced neurotoxicity.…”
Section: Discussioncontrasting
confidence: 75%
“…This is partially due to the fact that after its identification, it was found that several cancer cell lines and primary cancer cells gained TRAIL resistance [ 7 ]. Moreover, it has been reported that TRAIL-R2 can also have pro-oncogenic properties, such as in cancer cells with oncogenic mutations in the Kirsten rat sarcoma virus (KRAS) [ 8 ] or wild-type p53 gene [ 9 ]. Therefore, a better understanding of the cancer cell TRAIL/TRAIL-R apoptosis mechanism and gained resistance will be crucial for the development of TRAIL-related anti-cancer drugs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that both TRAIL-R2 and DcR1 receptors are p53 target genes [ 29 ] and, while is clear that TRAIL-R2 upregulation depend upon p53 activation [ 46 ], the requirement of TRAIL-R2 during p53-mediated apoptosis remains still unclear. However, more recently, nuclear TRAIL-R2 has been shown to act as a negative regulator of p53, suggesting that it may heavily impact, for example, tumour growth [ 47 ]. Despite these findings, we found that the p53 expression was blunted in TRAIL-R −/− mice treated with oligomeric Aβ1-42, suggesting that TRAIL-R2 contributes, in turn, to p53 mediation of Aβ-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%